Experimental data for loads on tunnel linings including distributed optical fiber sensing and digital image correlation - Jansson, August (Chalmers University of Technology, 2024)
The data is collected during experiments that aims to reproduce loading conditions in shotcrete tunnel linings. The data includes strain measurements from distributed optical fiber sensors, image series taken simultaneously by two cameras for digital image correlation purposes and load-, displacement- and pressure measurements by load cells, LVDTs and pressure gauges respectively. Supplementary data including material testing and 3D-scans before and after each run is also included. The material testing data includes concrete cube compression tests, wedge splitting tests and tensile tests of cores drilled from the main specimens. A detailed description of the experimental setup and execution is described in the data paper:

Datan har insamlats under laboratorieexperiment som syftar till att återskapa lokala lastförhållanden i sprutinklädda tunnlar. Inkluderat i datasettet töjningsmätningar från utrbredd fiberoptisk monitorering, bildserier för två kameror som tog kontinuerliga bilder av provkropparnas yta för användning av DIC och last-,förskjutning- och tryckmätningar från lastceller, LVDTer och tryckceller. Utöver mätdatan är kompletterande 3D-skanningar tagna innan och efter varje försök, samt materialtester inkluderade. Utförda materialtester är tryckprovning av kuber, "wedge-splitting tests" och dragförsök för borrade kärnor. Mer detaljerad beskrivning av de utförda experimenten återfinns i data-artikeln:
Experimentellt dataset för laster på tunnelinklädnader med utbredd fiberoptisk monitorering och digital bildkorrelation
Keywords: tunnel construction; tunnelbyggnad; load-bearing structures; bärande konstruktioner; fibre optics; fiberoptik; concrete; betong; shotcrete; sprutbetong; Infrastructure Engineering; Infrastrukturteknik